CXCL10, MCP-1, and Other Immunologic Markers Involved in Neural Leprosy. Issue 3 (March 2015) - Medeiros, Mildred F.; Rodrigues, Márcia M. J.; Vital, Robson T.; da Costa Nery, José A.; Sales, Anna M.; de Andrea Hacker, Mariana; Ferreira, Helen; Chimelli, Leila; Sarno, Euzenir N.; Antunes, Sérgio L. G.
<x xml:space="preserve">Abstract</x> Nerve damage in leprosy can be directly induced by Mycobacterium leprae in the early stages of infection, however, immunomediated mechanisms add gravity to the impairment of neural function in symptomatic periods of the disease. This study investigated the immunohistochemical expression of immunomarkers involved in the pathogenic mechanisms of leprosy nerve damage. These markers selected were CXCL10, CCL2 chemokines and immunomarkers as CD3, CD4, CD8, CD45RA, CD45RO, CD68, HLA-DR, and metalloproteinases 2 and 9 (MMP2 and MMP9) occurring in nerve biopsy specimens collected from leprosy (23) and nonleprosy patients (5) suffering peripheral neuropathy. CXCL10, CCL2, MMP2, and MMP9 immunoreactivities were found in the leprosy nerves but not in nonleprosy samples. Immunolabeling was predominantly found in recruited macrophages and Schwann cells composing the inflammatory cellular population in the leprosy-affected nerves. The immunohistochemical expression of all the markers, but CXCL10, was associated with fibrosis, however, only CCL2 was, independently from the others, associated with this excessive deposit of extracellular matrix. No difference in the frequency of the immunolabeling was detected between the AFB+ and AFB− leprosy subgroups of nerve, exception made to some statistical trend to difference in regard to CD68− and HLA-DR+ cells in the AFB− nerves exhibiting epithelioid granuloma. MMP9 expression associated with fibrosis is consistent with previous results of research group. The findings conveys the idea that CCL2 and CXCL10 chemokines at least in advanced stages of leprosy nerve lesions are not determinant for the establishment of AFB+ or AFB− leprosy lesions, however, CCL2 is associated with macrophage recruitment and fibrosis.